The delayed cortisol peak effect after severe burn injury: a prospective observational study - Bamberg, Maximilian; Maros, Máté E.; Menger, Maximilian Michael; Thiel, Johannes Tobias; Illg, Claudius; Viergutz, Tim; Kalenka, Armin; Fontana, Johann (In vivo, 2025)
Background/Aim: In contrast to patients with major trauma and septic shock, little is known about the incidence and relevance of acute adrenal insufficiency among patients with burn injuries. Addressing this data gap, the current study was designed to analyze the spontaneous cortisol stress response after severe burn injury. - Patients and Methods: The study was designed as a prospective observational analysis. From 09/2023 until 06/2024, all patients admitted to the Intensive Care Unit of the BG Tübingen Burn Center were included. The daily cortisol levels were determined in combination with the daily routine laboratory values between 5 and 6 a.m. from day 1 until 7. The data acquisition included the following parameters: Age, sex, total body surface area (TBSA) burned, Abbreviated Burn Severity Index (ABSI), tracheotomy, inhalation trauma, serum cortisol, interleukin-6 (IL-6), leukocyte count and C-reactive protein (CRP). - Results: A total of 19 patients with a mean TBSA burned of 33.58±22.68% were included. The mean cortisol values from days 1 to 4 stayed within the physiological range with a delayed significant increase from day 5 until 7 (day 1: 503.3±279.5 vs. day 7: 812.5±330.6 nmol/l; physiological range=130-630 nmol/l). TBSA burned, ABSI, and third-degree injury failed to demonstrate predictive potential, while the IL-6 and leukocyte courses demonstrated significant correlation with the cortisol course. - Conclusion: The findings of the current study align with previous studies suggesting a relative cortisol deficit during the acute stages of severe burn injury, supporting the treatment approach of early low-dose hydrocortisone supplementation in patients with severe burn injury.
Online veröffentlicht: März 2025
Gesehen am 13.06.2025